Legal Counselling and Communication Campaign On The Dangers of Hoaxes In Social Media By The Women’s Empowerment Forum (FPPI), Bali Province - Ani Purwati; Marlinda Irwanti; Aris Yulia; Gita Ruslita (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2025)
The massive spread of hoaxes through social media has become a serious challenge in Indonesia, as it not only disrupts individual understanding but also threatens social harmony and legal certainty. This community service program, organized by the Women’s Empowerment Forum (FPPI) Bali Province, aimed to raise public awareness of the dangers of hoaxes while providing legal knowledge regarding the consequences faced by those who disseminate false information. The program was carried out through a combination of legal counselling and participatory communication campaigns with a local cultural approach. The legal counselling materials included the regulatory framework governing hoaxes, their social impacts, and strategies for early detection and prevention. Meanwhile, the communication campaign utilized posters, infographics, digital content, as well as cultural expressions such as traditional poetry (pantun) and Balinese performing arts, making the legal messages easier to understand and more engaging. Participants, consisting of women, youth, students, and community leaders, were actively involved in discussions, simulations, and group campaigns. The results of the program indicated an increased understanding among participants regarding the legal implications of spreading hoaxes and improved ability to identify misleading information in the digital sphere. This program demonstrates that participatory community-based strategies, when combined with legal literacy and cultural communication, can strengthen both digital awareness and social resilience against hoaxes. The initiative also reflects the role of higher education institutions in fulfilling the Tri Dharma of universities through legal education, community empowerment, and the promotion of responsible digital citizenship.